A recombinant multi-antigen vaccine formulation containing Babesia bovis merozoite surface antigens MSA-2a1, MSA- 2b and MSA-2c elicits invasion-inhibitory antibodies and IFN-γ producing cells - Gimenez, Alba Marina; Françoso, Katia S.; Ersching, Jonatan; Icimoto, Marcelo Y.; Oliveira, Vitor; Rodriguez, Anabel Elisa; Schnittger, Leonhard; Florin-Christensen, Mónica; Rodrigues, Mauricio M.; Soares, Irene S. (2017)
Background: Babesia bovis is a tick-transmitted protozoan hemoparasite and the causative agent of bovine babesiosis, a potential risk to more than 500 million cattle worldwide. The vaccines currently available are based on attenuated parasites, which are difficult to produce, and are only recommended for use in bovines under one year of age. When used in older animals, these vaccines may cause life-threatening clinical symptoms and eventually death. The development of a multi-subunit recombinant vaccine against B. bovis would be attractive from an economic standpoint and, most importantly, could be recommended for animals of any age. In the present study, recombinant ectodomains of MSA-2a1, MSA-2b and MSA-2c antigens were expressed in Pichia pastoris yeast as secreted soluble peptides. Results: The antigens were purified to homogeneity, and biochemically and immunologically characterized. A vaccine formulation was obtained by emulsifying a mixture of the three peptides with the adjuvant Montanide ISA 720, which elicited high IgG antibody titers against each of the above antigens. IgG antibodies generated against each MSA-antigen recognized merozoites and significantly inhibited the invasion of bovine erythrocytes. Cellular immune responses were also detected, which were characterized by splenic and lymph node CD4+ T cells producing IFN-γ and TNF-α upon stimulation with the antigens MSA-2a1 or MSA-2c.